Coronary stent symmetry and vascular injury determine experimental restenosis. Issue 4 (1st April 2000) - Schulz, C; Herrmann, R A; Beilharz, C; Pasquantonio, J; Alt, E
Abstract : OBJECTIVE: To assess the impact of stent symmetry on restenosis using the coronary overstretch sheep model. METHODS: Neointimal thickness, injury index, and percentage diameter and area stenosis were calculated by digital morphometry. The standard deviation of the angular burden was used to assess stent symmetry for each section. MATERIALS: 15 healthy Merino sheep (63–75 kg) underwent implantation of 30 slotted tube stents (7 mm). Restenosis was induced by calculated overstretch of the coronary artery. Twenty eight days after implantation, stents were excised and underwent histological examination using quantitative digital morphometry. RESULTS: The severity of vessel injury was positively correlated with neointimal thickness and with percentage diameter and area stenosis (p < 0.001). Mean neointimal thickness and mean vascular injury per cross section were strongly related to the standard deviation of angular burden, with correlation coefficients of 0.6 and 0.8, respectively (p < 0.001). CONCLUSIONS: The well known relation between vascular injury and restenosis was confirmed, and a new relation was discovered between stent asymmetry and restenosis. If these results apply to human coronary arteries, restenosis may also be dependent on the degree of asymmetric stent expansion. These results should influence the development of new stent designs to reduce asymmetric stent expansion, leading to a more homogeneous strain distribution in stented coronary segments.